RANCANG BANGUN SISTEM PENDING ONGKOS ANGKUT PADA DEPARTEMEN VERIFIKASI AKUNTANSI PT PUPUK SRIWIDJAJA PALEMBANG - Erlin Lilis; Muhamad Son Muarie (Jurnal Riset Sistem Informasi, 2026)
Financial document verification is an essential part of a company’s internal control system to ensure the accuracy, validity, and reliability of financial reporting. At PT Pupuk Sriwidjaja Palembang, the verification process for freight cost documents is still carried out manually using Google Spreadsheets, which causes several issues such as the loss of document history, difficulties in tracking document status, and delays in the verification process due to ineffective interdepartmental coordination. This study aims to design and develop an integrated Freight Cost Pending System to support a more structured and transparent document verification process. The research method applied is Object Oriented Analysis and Design (OOAD) with a prototype development approach. Data were collected through observation, informal interviews, documentation studies, and literature reviews. The results indicate that the developed system is able to record document status and history in real time, improve verification efficiency, minimize the risk of data loss, and strengthen coordination between the Accounting Verification Department and the Marketing and Sales Administration Department